2022
DOI: 10.5334/gh.1140
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Screening and Management of Dysglycemia among Patients Presenting with Acute Myocardial Infarction in North India: The Prospective NORIN STEMI Registry

Abstract: Background: Dysglycemia is a major and increasingly prevalent cardiometabolic risk factor worldwide, but is often undiagnosed even in high-risk patients. We evaluated the impact of protocolized screening for dysglycemia on the prevalence of prediabetes and diabetes among patients presenting with ST-segment elevation myocardial infarction (STEMI) in North India. Methods:We conducted a prospective NORIN STEMI registry-based study of patients presenting with STEMI to two government-funded tertiary care medical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Tsuchida et al 14 reported 17% of the 298 patients studied had newly diagnosed DM, which was not a predictor of up to 10-year cardiovascular disease risk. Other studies focused on only STEMI patients 15 , 16 . Therefore, newly diagnosed DM seemed to have greater short-term impact and less long-term impact according to the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tsuchida et al 14 reported 17% of the 298 patients studied had newly diagnosed DM, which was not a predictor of up to 10-year cardiovascular disease risk. Other studies focused on only STEMI patients 15 , 16 . Therefore, newly diagnosed DM seemed to have greater short-term impact and less long-term impact according to the above studies.…”
Section: Discussionmentioning
confidence: 99%